Imaging Flow Cytometry: Methods and Protocols - Barteneva, Natasha S.; Vorobjev, Ivan A. (Methods in molecular biology, 2016)
Quantitative Functional Morphology by Imaging Flow Cytometry -- Principles of Amnis Imaging Flow Cytometry -- Ultrafast Microfluidic Cellular Imaging by Optical Time-Stretch -- Applications of Imaging Flow Cytometry for Microalgae -- The Analysis of Cell Cycle, Proliferation, and Asymmetric Cell Division by Imaging Flow Cytometry -- Quantitation of Chromosome Damage by Imaging Flow Cytometry -- Fluorescent In Situ Hybridization In Suspension by Imaging Flow Cytometry -- Analysis of Nucleo-Cytoplasmic Protein Shuttling by Imaging Flow Cytometry -- Using Image-Based Flow Cytometry with a FISH-Based FlowRNA Assay to Simultaneously Detect Intracellular TNF-α Protein and mRNA in Monocytes Following LPS Stimulation -- Multiparametric Characterization of Human T-Cell Immune Synapses by InFlow Microscopy -- Studying T Cells N-Glycosylation by Imaging Flow Cytometry -- Assessment of Granulocyte Subset Activation: New Information from Image-Based Flow Cytometry -- Using Image-Based Flow Cytometry to Assess Monocyte Oxidized LDL Phagocytosis Capacity -- Screening for Drugs Against the Plasmodium falciparum Digestive Vacuole by Imaging Flow Cytometry -- Accurate Assessment of Cell Death by Imaging Flow Cytometry -- Temporal Heterogeneity in Apoptosis Determined by Imaging Flow Cytometry -- FlowCAM: Quantification and Classification of Phytoplankton by Imaging Flow Cytometry -- Detection and Characterization of Rare Circulating Endothelial Cells by Imaging Flow Cytometry -- Imaging Flow Cy tometric Analysis of Primary Bone Marrow Megakaryocytes -- Sickle Cell Imaging Flow Cytometry Assay (SIFCA).